Broad‐spectrum and sensitive screening of more than 1000 compounds in equine urine using liquid chromatography/high‐resolution mass spectrometry - Uchida, Taiga; Kisugi, Takaya; Ishii, Hideaki; Yamada, Masayuki; Kinoshita, Kenji; Leung, Gary Ngai‐Wa (Rapid communications in mass spectrometry, 2024)
Rationale To uphold the integrity of horseracing and equestrian sports, it is critical for an equine doping control laboratory to develop a comprehensive screening method to cover a wide range of target substances at the required detection levels in equine urine. Methods The procedure involved the enzymatic hydrolysis of 3 mL urine samples followed by solid‐phase extraction using HF Bond Elut C18 cartridge. The resulting extracts were then separated on a C18 reversed‐phase column and analyzed using liquid chromatography/high‐resolution mass spectrometry (LC/HRMS) in both electrospray ionization positive and negative modes in two separate injections. The analytical data were obtained in full scan and product ion scan (PIS) modes in an 11 min LC run. Results The method can detect 1011 compounds (in both positive and negative ion modes). Over 95% of the target compounds have limits of detections (LODs) ≤10 ng/mL, and more than 50% of the LODs are ≤0.5 ng/mL. The lowest LOD can reach down to 0.01 ng/mL. The applicability of the method was demonstrated by the successful detection of prohibited substances in overseas and domestic equine urine samples. Conclusions We have successfully developed a regular screening method for equine urine samples that can detect more than 1000 compounds at sub‐ppb levels in both positive and negative ion modes with full scan and PIS using LC/HRMS. Furthermore, this method can theoretically be expanded to accommodate an unlimited number of prohibited substances in full‐scan mode.